Simplified Model of Soil-Structure Interaction for Seismically Isolated Containment Buildings in Nuclear Power Plant. (May 2017) - Ashiquzzaman, Md; Hong, Kee-Jeung
Abstract: This study presents a significant effect of soil-structure-interaction (SSI) on seismically isolated containment buildings in nuclear power plant (NPP) during very strong ground motion. In this research it is considered that the containment building is founded on an elastic layer of soil with negligible foundation depth. The complete system of containment building in nuclear power plant is expressed by a simplified model consisting five degrees of freedom (5-DOF). In this study rotational degree of freedom of the isolation mass is the new inclusion in the proposed simplified SSI model. The equations of motion are developed based on that proposed simplified model in order to define the modal characteristics of the model. Now foundation mass does not show any dynamic behavior since zero mass is considered, therefore an equivalent three degree of freedom (3-DOF) system is explained as a different SSI parameter of the containment building. In the modal analysis, the horizontal isolation mode is enough to describe the whole system of the model. This paper performs extensive parametric studies to express the effect of soil structure interaction on containment building in nuclear power plants.